THE ART OF ONLINE TEACHING: A LOOK AT SOME OF THE ONLINE TEACHING METHODS - Geevarghese, Keya Sara; P.P.Vijayalaksmi, (International Journal of Psychosocial Rehabilitation, 2020)
Technology has impacted almost every aspect of our lives today and education is no exception. Online learning has become one of the most imperial parts of education. Online learning is an internet based educational process whereby a learner learns through interaction with the educator via technological means. It is also referred to as e-learning. Online learning also comes under the distance learning process. Our education system focus on the process whereby the teacher stands on a podium and lectures in front of the whole group of students while the students sit, try to comprehend and make notes at the same time. This process required a multitasking from students whereby a student was expected to listen and prepare notes at the same time which often led to confusion later while referring to the text for exams. In online learning no such multitasking is required. A student can actually listen to the classes almost anytime according to his or her convenience and can jot down the notes whenever he feels light and in this way online teaching has gained an upper hand in recent times. As Seymour Papert notes, “You can’t teach people everything they need to know. The best you can do is position them where they can find what they need to know when they need to know it.” Today a massive amount of information are available at one’s fingertips through the internet and opportunities for formal learning are available online worldwide through application and websites. Thus Access to classes on learning has actually become independent or little easy for students.